The FEM model of groundwater circulation in the vicinity of the Świniarsko intake, near Nowy Sącz (Poland) - Zdechlik, Robert; Kałuża, Agnieszka (Geologos, 2019)
Modern hydrogeological research uses numerical modelling, which is most often based on the finite difference method (FDM) or finite element method (FEM). The present paper discusses an example of application of the less frequently used FEM for simulating groundwater circulation in the vicinity of the intake at Świniarsko near Nowy Sącz. The research area is bordered by rivers and watersheds, and within it, two well-connected aquifers occur (Quaternary gravelly-sandy sediments and Paleogene cracked flysch rocks). The area was discretized using a Triangle generator, taking into account assumptions about the nature and density of the mesh. Rivers, wells, an irrigation ditch and infiltration of precipitation were projected onto boundary conditions. Conditions of groundwater circulation in the aquifer have been assessed based on a calibrated model, using water balance and a groundwater level contour map with flow path lines. Application of the program based on FEM, using smooth local densification of the discretization mesh, has allowed for precise mapping of the location of objects that significantly shape water circulation.